U.S. class action lawsuits targeting foreign firms: The country spillover effect - Huang, Xuxing; Rui, Yixuan; Shen, Jianfeng; Tian, Gloria Y. (Journal of Corporate Finance, 2017)
We find negative price reactions among non-sued U.S.-listed foreign firms to filings of U.S. shareholder lawsuits targeting firms from their home country. This country spillover effect is stronger for lawsuits, especially accounting-related ones, targeting firms from more poorly-governed countries. We also document a stronger country spillover effect for a recent wave of U.S. lawsuits targeting Chinese issuers than for other standalone litigation. Finally, a foreign firm's price reaction to lawsuits targeting its country peers predicts its chance of being sued in the future. Our findings are consistent with investors updating a foreign firm's litigation risk upon lawsuits targeting its country peers.